Practical switching power supply design - Brown, Marty, 1951-; Elsevier Science Publishers (San Diego : Academic Press, 1990)
Take the "black magic" out of switching power supplies with Practical Switching Power Supply Design! This is a comprehensive "hands-on" guide to the theory behind, and design of, PWM and resonant switching supplies. You'll find information on switching supply operation and selecting an appropriate topology for your application. There's extensive coverage of buck, boost, flyback, push-pull, half bridge, and full bridge regulator circuits. Special attention is given to semiconductors used in switching supplies. RFI/EMI reduction, grounding, testing, and safety standards are also detailed. Numerous design examples and equations are given and discussed. Even if your primary expertise is in logic or microprocessor engineering, you'll be able to design a power supply that's right for your application with this essential guide and reference! Key Features * Gives special attention to resonant switching power supplies, a state-of-the-art trend in switching power supply design * Approaches switching power supplies in an organized way beginning with the advantages of switching supplies and thier basic operating principles * Explores various configurations of pulse width modulated (PWM) switching supplies and gives readers ideas for the direction of their designs * Especially useful for practicing design engineers whose primary specialty is not in analog or power engineering fields.
Why use switching power supplies? -- How a switching power supply works -- A walk through a representative switching power supply -- Switching power supply topologies -- Semiconductors used in a switching power supply -- The magnetic components within a switching power supply -- Cross-regulation of the outputs -- Protection -- Miscellaneous topics -- Closing the loop-feedback and stability -- Resonant converters -- an introduction -- Switching power supply design examples.
Includes bibliographical references (p. 235-236) and index.
Keywords: Switching circuits -- Design and construction; Power semiconductors -- Design and construction; Semiconductor switches -- Design and construction; Switching power supplies -- Design and construction; Electronic books